Noncoding RNAs as therapeutic targets in early stage diabetic kidney disease - Mitsuo Kato (The Korean Society of Nephrology, 2018)
Diabetic kidney disease (DKD) is a major renal complication of diabetes that leads to renal dysfunction and end-stage renal disease (ESRD). Major features of DKD include accumulation of extracellular matrix proteins and glomerular hypertrophy, especially in early stage. Transforming growth factor-β plays key roles in regulation of profibrotic genes and signal transducers such as Akt kinase and MAPK as well as endoplasmic reticulum stress, oxidant stress, and autophagy related to hypertrophy in diabetes. Many drugs targeting the pathogenic signaling in DKD (mostly through protein-coding genes) are under development. However, because of the limited number of protein-coding genes, noncoding RNAs (ncRNAs) including microRNAs (miRNAs) and long noncoding RNAs (lncRNAs) are attracting more attention as potential new drug targets for human diseases. Some miRNAs and lncRNAs regulate each other (by hosting, enhancing transcription from the neighbor, hybridizing each other, and changing chromatin modifications) and create circuits and cascades enhancing the pathogenic signaling in DKD. In this short and focused review, the functional significance of ncRNAs (miRNAs and lncRNAs) in the early stages of DKD and their therapeutic potential are discussed.